2005
DOI: 10.1183/09031936.04.00086104
|View full text |Cite
|
Sign up to set email alerts
|

Oral L-arginine supplementation in cystic fibrosis patients: a placebo-controlled study

Abstract: Exhaled nitric oxide (eNO) is decreased in cystic fibrosis (CF). The effect of oral Larginine, the precursor of enzymatic nitric oxide (NO) formation, on airway NO in patients with CF was studied.In a pilot study, oral L-arginine was given in a single dose of 200 mg?kg -1 body weight to eight healthy controls and eight CF patients. Subsequently, the same L-arginine dose was given to 10 patients with CF (five females) t.i.d. for 6 weeks in a randomised double-blind placebo-controlled crossover study.A single do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…We also showed that the statistical significance of the relationship was lost in patients receiving inhaled corticosteroids. Our results suggest that NO deficiency in conducting airways may participate in bronchial obstruction since GRASEMANN et al [24] have shown that nebulised L-arginine not only significantly increased exhaled NO concentration but also resulted in a sustained improvement of FEV1 in patients with CF. Interestingly, in this latter study, oxygen saturation also increased significantly after the inhalation of L-arginine, which suggests an effect of NO on V9/Q9 matching (we found a relationship between Pa,O 2 and J'aw,NO) [24].…”
Section: Cystic Fibrosis and Non-cystic Fibrosis Bronchiectasis D Humentioning
confidence: 60%
“…We also showed that the statistical significance of the relationship was lost in patients receiving inhaled corticosteroids. Our results suggest that NO deficiency in conducting airways may participate in bronchial obstruction since GRASEMANN et al [24] have shown that nebulised L-arginine not only significantly increased exhaled NO concentration but also resulted in a sustained improvement of FEV1 in patients with CF. Interestingly, in this latter study, oxygen saturation also increased significantly after the inhalation of L-arginine, which suggests an effect of NO on V9/Q9 matching (we found a relationship between Pa,O 2 and J'aw,NO) [24].…”
Section: Cystic Fibrosis and Non-cystic Fibrosis Bronchiectasis D Humentioning
confidence: 60%
“…Addition of acidified nitrite, which can generate NO either spontaneously or from NIR activity, was found to effectively control P. aeruginosa, S. aureus and Burkholderia cepacia biofilms [124,125], although in these cases high concentrations of nitrite (15 mM) were used and NO acted via a toxic, killing effect on biofilms. In preliminary clinical studies, treatments with nebulized L-arginine in CF patients infected with P. aeruginosa resulted in sustained improvement in lung function associated with significantly increased NOS activity within lung tissues, suggesting that the NO augmentation could potentially reduce the bacterial infection [126,127]. However in these studies, the effect of increased L-arginine on P. aeruginosa growth was not investigated and will need to be confirmed in subsequent trials.…”
Section: Stimulation Of Endogenous No Productionmentioning
confidence: 97%
“…In a rodent model, L-arginine was associated with reduced tissue damage, decreased neutrophil recruitment, and reduced IL-1b (Hopkins et al 2006). A small study of L-arginine in CF was associated with increased eNO (Grasemann et al 2005b). L-Arginine has potential, but large prospective clinical trials have not been performed.…”
Section: Modulators Of Intracellular Signalingmentioning
confidence: 99%